2020
DOI: 10.3390/plants9081024
|View full text |Cite
|
Sign up to set email alerts
|

Framework Phylogeny, Evolution and Complex Diversification of Chinese Oaks

Abstract: Oaks (Quercus L.) are ideal models to assess patterns of plant diversity. We integrated the sequence data of five chloroplast and two nuclear loci from 50 Chinese oaks to explore the phylogenetic framework, evolution and diversification patterns of the Chinese oak’s lineage. The framework phylogeny strongly supports two subgenera Quercus and Cerris comprising four infrageneric sections Quercus, Cerris, Ilex and Cyclobalanopsis for the Chinese oaks. An evolutionary analysis suggests that the two subgenera proba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 72 publications
(140 reference statements)
1
2
0
Order By: Relevance
“…Within the section Cyclobalanopsis, Q. gilva and Q. sichourensis did not form a CTB lineage sister to the STB lineage, as demonstrated in previous studies (Deng et al 2018;Hipp et al 2020;Yang et al 2020). Our results showed that the phylogenetic position of Q. ningangensis was located between Q. sichourensis and Q. acuta.…”
Section: Chloroplast Sequence Variation and Evolutionsupporting
confidence: 83%
See 1 more Smart Citation
“…Within the section Cyclobalanopsis, Q. gilva and Q. sichourensis did not form a CTB lineage sister to the STB lineage, as demonstrated in previous studies (Deng et al 2018;Hipp et al 2020;Yang et al 2020). Our results showed that the phylogenetic position of Q. ningangensis was located between Q. sichourensis and Q. acuta.…”
Section: Chloroplast Sequence Variation and Evolutionsupporting
confidence: 83%
“…It has four trichome types, including fasciculate, simple stellate, appressed lateral attached, and uniseriate, which is one of the most diversified in this section (Deng et al 2014). However, recent phylogenetic and phylogenomic studies have not included samples of this species (Deng et al 2018;Hipp et al 2020;Yang et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the phylogenetic relationships of species in this group based on a few markers (e.g. Yang et al, 2017Yang et al, , 2020 or reduced-representation genomic data (RAD-seq) (Jiang et al, 2019;Hipp et al, 2020), and many topological conflicts were found among them, even when using the same type of dataset. Extensive introgression among these species and ILS may be the reasons for their unresolved relationships.…”
Section: Introductionmentioning
confidence: 99%